Pathomorphological and Immunohistochemical Study of Fibrosarcoma in an Adult Dog: A Case Report - , Paras Saini; , Babu Lal Jangir; , Gulshan Narang; , Rakshita Sharma; Priyanka, (Archives of Current Research International, 2024)
Aim: The objective of the present case report is to describe pathomorphological findings and immunohistochemical expression of pancytokeratin (PCK), vimentin, proliferating cell nuclear antigen (PCNA) and Ki67 in a case of fibrosarcoma in dog. Case Presentation: A large, round ball-like growth of approximately 14 centimetres in diameter was noticed on caudal aspect of left thigh region in ten years old male bull dog. Its surface was ulcerated. It was soft in consistency and cut surface appeared pinkish-white. Giemsa-stained smears revealed spindle cells with elongated nuclei containing granular chromatin, single to multiple nucleoli and scanty cytoplasm. Histopathological examination revealed moderately to well-differentiated neoplastic fibroblasts arranged in interwoven pattern with the presence of collagenous stroma. Neoplastic cells were characterized by pleomorphic, oval to elongated nuclei with single to multiple prominent nucleoli and moderate to scanty cytoplasm. Mitotic count was 1.2/high power field. The Immunohistochemical staining revealed intracytoplasmic positive immunoreactivity for vimentin and no immunoreactivity for PCK. Proliferating neoplastic cells revealed mild to strong nuclear immunostaining for PCNA and Ki67 with 56.7% PCNA index and 4.0% Ki67 index. Conclusion: Based on histopathological findings, the case was diagnosed as fibrosarcoma. Immunopositive reactivity for vimentin and no immunoreactivity for PCK indicated the mesenchymal origin of the tumour. Histopathological features, low mitotic count and low Ki67 index suggested the less aggressive behaviour of the tumour in the present case.